Wine Label Descriptors and Shelf Price Paid by Argentine Consumers - García Arancibia, Rodrigo (2015)
A wide variety of wines are sold in the Argentine retail wine market, both in specialized stores and supermarkets. There are several wine segments according to their degree of vertical differentiation, each with additional differentiation strategies. One of them centers on the information provided in the bottle label to attract consumers, which can be characterized as objective information (type of grape, color, age, alcoholic content, region of origin) and additional information (food pairing, sensorial and environmental characteristics, wine making process, serving temperature suggestions). The question arises about the relationship, if any, between those descriptors and the price paid by the consumer. To answer it, an empirical study was conducted for Santa Fe city, an important consumption center. A hedonic price model was estimated, with the results showing that within the lower-priced wine segment, the additional information had a positive impact on prices; this situation was not the same for the higher-priced wines. Statistically significant differences were also found between provinces of origin, type of wine and purchase place.